The Place of Law in the Dialectical Interpretation of Reality - Radvilavičius, Vytautas (Problemos, 1969)
In the article the main features of the dialectical understanding of reality and of human cognition are characterized. There the dialectical interpretation of the fundamental concepts – repetition, necessity, essence, which determine law, is given. With respect to law, the accent is laid on it being a form of human cognition. In view of the dialectical picture of reality and human cognition clear factors, reflecting law in reality and at the same time its place in inte1pretation of reality, come to light. The dialectical materialistic understanding of the questions under study is given by way of parallel characterization of the metaphysical-materialistic concept on the same question. It is done with a view of dissociating strictly from the metaphysical understanding of law and its place in the scientific cognition of reality. Such dissociation is necessary at the present lime for the successful struggle against subjective conceptions of law, on the one hand, and is conducive to further progress of science, on the other hand.